Information, Managerial Choice and Stockholder Unanimity - Leland, H. (Review of Economic Studies, 1978)
Journal Article Information, Managerial Choice and Stockholder Unanimity Get access Hayne Leland Hayne Leland School of Business Administration University of California, Berkeley Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 3, October 1978, Pages 527–534, https://doi.org/10.2307/2297254 Published: 01 October 1978 Article history Received: 01 July 1976 Accepted: 01 June 1977 Published: 01 October 1978